Elliott and Quinn's Tort Law - Frances Quinn, Catherine Elliott (United Kingdom Pearson, 2019)
This text aims to provide a clear explanation of tort law. As well as setting out the law itself, it also examines the principles behind it and discusses some of the issues and debates arising from it. All key areas of tort law are covered, along with topical debates in those fields. Recent developments that are considered include the litigation arising from the Hillborough football disaster and the case of Page versus Smith (1995). Additionally, there are detailed guidlines at chapter ends on answering typical examination questions, as well as a chapter of general advice.
Keywords: Torts; Law; (ASB-2400) Law for Business